Analysis of stress’s effects on cardiac dynamics: A case study on undergraduate students - Cubillos-Calvachi, Juan; Piedrahita-Gonzalez, Juan; Gutierrez-Ardila, Carlos; Montenegro-Marin, Carlos; Gaona-Garcia, Paulo; Burgos, Daniel (International Journal of Medical Informatics, 2025)
Early detection of cardiovascular disease could make a difference in terms of treatment success. For that reason, it is important to test the reliability of tools used to deliver diagnoses and to measure the impact of external factors such as stressful situations on alterations in the data collected. Students are an interesting cohort for investigating the effects of stressful situations, as they have a variable number of stress-causing situations in their daily activity over a short period of time.
Basic procedure This investigation used 50 students, each of whom underwent two 21 -h tests involving the measurement of heart rate in beats per minute while they were carrying out their normal daily activities with their own tools. In this case study, we measured the impact of stressful situations with a tool for the self-diagnosis of cardiovascular diseases, using data from students on holiday and during their final exams. We asked the students to select two days on which to use the device and perform the test. The requirements for the days were given to them as follows: for the first test, the students were required to select a day off when their main activity was rest; for the second test, the students were required to select a day in their final exams week that they expected to be the hardest day with the most stressful situations. This paper describes a case study in which we measured the impact of stressful situations with the students’ own tools for the self-diagnosis of cardiovascular diseases, using data from students on holiday and during their final exams week. These two datasets, as well as the results of the diagnosis, were compared.
Keywords: Computer science; Medical informatics; Stress; Cardic arrest